DEVELOPMENT OF CHANNELS OF INTELLECTUAL CAPITAL MOVEMENT IN THE SYSTEM OF INNOVATIVE COOPERATION IN EDUCATION, SCIENCE AND PRODUCTION - N. A. Khashimova, M. L. Tursunkhodjaev (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article analyzes the ways of development of channels of intellectual capital movement between various spheres of the intellectual environment. The approaches to the organization of intellectual capital movement based on the study of the regulatory framework are considered. The system of monitoring the development of channels of intellectual capital movement is analyzed. A marketing strategy for the development of channels of intellectual capital movement and the main directions of a marketing strategy for the formation and use of intellectual capital are proposed